Neurolaw and moral competence of corruption offenders: A criminal law analysis - Zico Junius Fernando (Komisi Pemberantasan Korupsi, 2026)
This article examines the relevance and limits of neurolaw in assessing the moral competence of corruption offenders within criminal law. The study responds to the growing use of neuroscience in criminal justice while recognizing that corruption remains a deliberate abuse of entrusted power that must not be excused through biological reductionism. Using normative legal research with statutory, conceptual, and comparative approaches, this article analyzes the relationship between mens rea, moral competence, neurocognitive impairment, and proportional criminal responsibility. The study finds that neurolaw may assist courts in understanding exceptional cases involving serious impairment of impulse control, moral reasoning, or executive function, but it should not be treated as a general defense for corruption. In an Indonesian context, its use must be limited, carefully regulated, and supported by strict evidentiary safeguards, independent forensic assessment, judicial gatekeeping, and protection against elite impunity. The article argues that neurolaw is relevant not to weaken anti-corruption enforcement, but to refine the assessment of culpability in rare and scientifically verifiable circumstances. Therefore, neuroscience-based evidence should complement, not replace, legal proof of intent, accountability, and public trust protection.